2012
DOI: 10.1186/1471-2474-13-261
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the surgical treatment of proximal humeral fractures – a nationwide 23-year study in Finland

Abstract: BackgroundProximal humeral fractures are common osteoporotic fractures. Most proximal humeral fractures are treated non-surgically, although surgical treatment has gained popularity. The purpose of this study was to determine changes in the surgical treatment of proximal humeral fractures in Finland between 1987 and 2009.MethodsThe study covered the entire adult (>19 y) population in Finland over the 23-year period from 1st of January 1987 to 31st of December 2009. We assessed the number and incidence of surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 21 publications
5
50
0
2
Order By: Relevance
“…We found that the most common fixation method used was the locking plate system followed by prosthesis. As shown previously, the use of the locking plate method has increased rapidly compared to other methods, without clear evidence of its superiority [19,20,18,21]. In our sample, the most frequent fracture was two-part (62 %), which is more than twice the number in Edinburg where the one-part was leading with 49 % [9].…”
Section: Discussionmentioning
confidence: 43%
“…We found that the most common fixation method used was the locking plate system followed by prosthesis. As shown previously, the use of the locking plate method has increased rapidly compared to other methods, without clear evidence of its superiority [19,20,18,21]. In our sample, the most frequent fracture was two-part (62 %), which is more than twice the number in Edinburg where the one-part was leading with 49 % [9].…”
Section: Discussionmentioning
confidence: 43%
“…This includes the length of immobilisation and the timing and provision of physiotherapy for less severe fractures 25 and the use of surgery. 15,36,37 Additionally, technology is changing all the time and there are various pressures for early implementation of new fixation devices 15,37 and surgical techniques, for example. 38 Rationale for a trial comparing surgical with non-surgical treatment Surgery is rarely essential for these fractures and there is a clinical consensus that it is not needed for the majority of non-displaced or minimally displaced fractures.…”
Section: Evidence Underpinning Practicementioning
confidence: 99%
“…Ein häufig angewandtes Verfahren zur Behandlung dieser Frakturen ist die winkelstabile Plattenosteosynthese [16]. Hierbei profitiert die Frakturheilung von einer hohen Stabilität der Osteosynthese und einer reduzierten Beeinträchtigung der Vaskularität, ungeachtet der Primär-schädigung [5,12,34].…”
Section: Introductionunclassified